Protagonists of Production in Preindustrial European Literature (1700-1800) Male and Female Entrepreneurs, Craftspeople, and Workers - von Tschilschke, Christian; Schuchardt, Beatrice (Europaeische Aufklaerung in Literatur und Sprache, 2022)
What form did the portrayal of business owners, entrepreneurs, peasants, craftspeople and similar 'protagonists of production' take before it became the subject of negative assessments in the epoch of industrialization? Focusing on the European Enlightenment movement with a special emphasis on Spain, this volume sheds light on how both male and female ﬁgures working in production are represented by novels, plays, economic tracts and in the press. Literary scholars, historians, and economists analyse how those portrayals are related to the history of economic thought, 18th-century economic discourse, and enlightened Political Economy. With an epilogue by Deirdre McCloskey.